2008
DOI: 10.1152/ajprenal.00286.2007
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin II in the enhancement of ammonia production and secretion by the proximal tubule in metabolic acidosis

Abstract: Nagami GT. Role of angiotensin II in the enhancement of ammonia production and secretion by the proximal tubule in metabolic acidosis. Am J Physiol Renal Physiol 294: F874-F880, 2008. First published February 20, 2008 doi:10.1152/ajprenal.00286.2007.-Acidosis and angiotensin II stimulate ammonia production and transport by the proximal tubule. We examined the modulatory effect of the type 1 angiotensin II receptor blocker losartan on the ability of metabolic acidosis to stimulate ammonia production and secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 34 publications
(101 reference statements)
1
28
1
Order By: Relevance
“…Apical NHE3 is believed to be an important mechanism of PT apical ammonia secretion (30,42,43). NHE3 expression was not altered significantly as a result of PT-GS-KO in either the cortex or outer stripe of the outer medulla either under basal conditions or after acid loading (Fig.…”
Section: Effect Of Pt-gs-ko On Nbce1 Expression During Acid Loadingmentioning
confidence: 89%
See 1 more Smart Citation
“…Apical NHE3 is believed to be an important mechanism of PT apical ammonia secretion (30,42,43). NHE3 expression was not altered significantly as a result of PT-GS-KO in either the cortex or outer stripe of the outer medulla either under basal conditions or after acid loading (Fig.…”
Section: Effect Of Pt-gs-ko On Nbce1 Expression During Acid Loadingmentioning
confidence: 89%
“…Several studies have suggested that apical NHE3 is the primary mechanism of PT ammonia secretion (30,42,43). However, other studies have suggested that mechanisms other than NHE3 are important (51,52), and a recent study showed that PT-specific NHE3 deletion did not alter either basal or acidosis-stimulated renal ammonia excretion (37).…”
mentioning
confidence: 99%
“…After mice were given 0.3 M NH 4Cl in 2% sucrose water or 2% sucrose water alone for 18 h, renal cortical tissue was dissected from two mouse kidneys, and homogenates were prepared by homogenization in mannitol buffer using a rotator-stator homogenizer, followed by slow-speed centrifugation to remove debris, as described previously (24). After an aliquot for total protein processing was taken, the remainder of the supernatant of the crude homogenate was used to prepare BBMs (24) as described by Booth and Kenny (1) and modified by Karniski et al (12,13).…”
Section: Animalsmentioning
confidence: 99%
“…When tested in vitro, ANG II has concentration-dependent effects on tNH 3 production and transport by the proximal tubule (19,20). The stimulatory effect of ANG II on tNH 3 production rates is mediated by type 1 ANG II (AT 1 ) receptors, and this stimulatory effect is enhanced in proximal tubule segments derived from acid-loaded mice (22)(23)(24).Using in vitro microperfused mouse proximal tubules, we previously demonstrated that a short-term (18 h) NH 4 Cl acid challenge in vivo resulted in an increased stimulatory effect of ANG II on tNH 3 production (22). Nevertheless, it was unclear whether upregulation of the systemic renin-angiotensin system with acid loading (9, 10, 27) was responsible for the increased ammoniagenic response to ANG II of proximal tubule segments isolated from acid-loaded mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation